The investigation of effect of alpha lipoic acid against damage on neonatal rat lung to maternal tobacco smoke exposure - Guzel, Elif Erdem; Kaya, Nalan; Ozan, Gonca; Tektemur, Ahmet; Dabak, Durrin Ozlem; Ozan, Ibrahim Enver (Elsevier Science Bv, 2018)
This study was carried out to determine the changes in the lungs of the rat pups exposed to tobacco smoke during pregnancy period and to investigate the protective effects of alpha lipoic acid, which is administered during pregnancy, on these changes. Spraque-Dawley female rats were divided into four groups: control, tobacco smoke (TS), tobacco smoke + alpha lipoic acid (TS + ALA) and alpha lipoic acid (ALA). The rats in control group were untreated. Rats were exposed to TS twice a day for one hour starting from eight weeks before mating and during pregnancy. 20 mg / kg of ALA was administered to rats. On 7th and 21st days 7 of the pups from each group were decapitated. Histological, morphometric, biochemical and quantitative real-time RT-PCR analyzes were performed. Histopathological and biochemical changes were observed in TS group. While a significant decrease was observed both in SP-A and VEGF immunoreactivities and mRNA levels, caspase-3 immunoreactivity and TUNEL positive cells were increased in TS group. It is suggested that prenatal TS exposure leads to morphological and histopathological changes on lung development by causing oxidative damage in lungs of neonatal rats and the maternal use of ALA can provide a limited protective effect on the neonatal lung development against this oxidative stress originating from TS. Although pregnant women are increasingly aware on health risks of smoking, environmental tobacco smoke exposure is still a widespread problem. For this reason, it is thought that this damage can be partially reduced by some antioxidant supplements in pregnancy.
Keywords: Alpha lipoic acid; Lung; Neonate; Tobacco smoke; Pregnancy